CANNABIS: PROBLEMS FACING THE STATE AND SOCIETY - MUSAEV , Djamaliddin (Тараққиёт тадқиқотлари: илмий-амалий анжуманлар материаллари тўплами, 2024)
The issue of how to deal with cannabis and related substances, the increase in their use and supply, and the associated consequences and problems, is a matter of much debate and has figured prominently in the international drug control debate in recent years.